Application of "Pepak Aksi" Media in Anti-Corruption Learning for Grade VII Students at SMPN 10 Malang City - Sunaryati, Yenni; Awaliyah, Siti; Untari, Sri (JED (Jurnal Etika Demokrasi), 2025)
Corruption remains a critical barrier to national development in Indonesia, particularly due to its systemic nature across public sectors. Despite anti-corruption programs mandated by law, including integration into civic and religious education, existing teaching approaches such as lectures often fail to actively engage students or effectively internalize ethical values. This study addresses the challenge by introducing “Pepak Aksi,” a card-based learning media designed to enhance anti-corruption education in junior high school settings. The objective of this study is to analyze the application and effectiveness of “Pepak Aksi” in fostering students’ understanding and internalization of anti-corruption values, specifically among Grade VII students at SMPN 10 Malang City. Employing a qualitative case study approach, data were collected through observations, in-depth interviews, and document analysis. The findings show that “Pepak Aksi” improves student engagement, enhances comprehension of anti-corruption concepts, and encourages the development of integrity, honesty, and discipline. Students demonstrated better performance in both academic tasks and behavioral indicators, while teachers reported improved instructional delivery and classroom dynamics. In conclusion, “Pepak Aksi” is an effective pedagogical tool for anti-corruption education, offering a participatory and values-oriented alternative to conventional methods. Its implementation contributes to the broader effort of character education and can be adapted for wider use in school curricula.